Community Career Counselling for Rural Transitions - Cahill, Mildred; Martland, Sandra (Canadian Journal of Counselling and Psychotherapy, 2007)
Strategies adopted to address crises in rural communities often focus on the individual. An alternative approach is proposed whereby the community is viewed as the client. Community career counselling requires the commitment of community members to engage in exploring, analyzing, deciding and acting on options. The counsellor's role as team member and facilitator can bridge the gap between individual career counselling and economic development of the community. Goal-setting, career exploration, and action-planning become the process and the outcome measures.